Community Satisfaction Index for the Implementation of the Karawang Berseri Program by PT. Pertamina EP Tambun Field in Karawang Kulon Sub-District - Wazirul Luthfi; Juniati Gunawan (Journal of Social Research, 2023)
The Karawang community is faced with the problem of poverty so other problems arise such as violence that occurs against women and children. Based on P2TP2A data, it shows that the level of violence against women and children continues to increase every year. To solve existing problems, PT Pertamina EP Tambun Field seeks to improve the quality of life and reduce violence against women and children through the Karawang Berseri CSR program. This study aims to determine the Community Satisfaction Index for the implementation of community empowerment programs in the Karawang Berseri program. The research method used is a descriptive qualitative method with case studies. Primary data was obtained through a survey of 134 respondents using the Saturated Sampling method and in-depth interviews with 12 beneficiary respondents. Secondary data was obtained from program planning documents, implementation reports, and monitoring and evaluation data. This research starts from May to June 2023 and is located in the Karawang Kulon Village. The results showed that of the 10 variables measured, it produced an average Community Satisfaction Index of 88.9, which indicated that the quality value of the Karawang Berseri program was A or Very Good. Some of the positive impacts can be seen from the economic, social, and environmental benefits that have been generated, and show that the company's commitment is very good and carrying out its responsibilities to society. The key to the success of this program lies in the participatory empowerment model both in planning, implementing, as well as monitoring and evaluation.